Molecular Characterization and Expression Analysis of a Novel Glutaredoxin 3 Gene in Pacific White Shrimp (Litopenaeus vannamei) - Peihua Zheng; Peihua Zheng; Xiuxia Zhang; Xiuxia Zhang; Dongmei Wang; Dongmei Wang; Juntao Li; Juntao Li; Zelong Zhang; Zelong Zhang; Yaopeng Lu; Yaopeng Lu; et al. (Frontiers in Marine Science, 2021)
Glutaredoxins (Grxs), small heat-stable oxidoreductases, are key members of the thioredoxin (Trx) superfamily. Recently, an emerging subclass of Grxs with a cysteine residue in the active site was found in shrimps. However, molecular functions of Grx-related proteins in decapods were rarely reported. In this study, a novel full-length Grx 3 (LvGrx 3) complementary DNA (cDNA) was identified in Pacific white shrimp (Litopenaeus vannamei), which had a 975-bp open reading frame (ORF) encoding a polypeptide of 324 amino acids. The nucleic acid sequence of Pacific white shrimp glutaredoxin 3 (LvGrx 3) showed 99.59% identity with genomic DNA (gDNA) sequence and 63.49% coverage. Sequence alignment showed that the amino acid sequence of LvGrx 3 shared 97% identity with black tiger shrimp (Penaeus monodon) Grx 3 and 62% identity with amphipod (Hyalella azteca) Grx 3. LvGrx 3 showed higher expression in the intestine, gill, and hepatopancreas, and lower expression in epithelium and abdominal nerve. In response to ammonia-N stress, LvGrx 3 was significantly upregulated in both the hepatopancreas and gill, and the peak value appeared after 24 h exposure. After lipopolysaccharide (LPS) injection, expression levels of LvGrx 3 in the hepatopancreas were increased in the middle stage, and LvGrx 3 in gill was upregulated in the middle and later periods (24 and 48 h). These results indicate that LvGrx 3 can participate in immune responses against ammonia-N stress and pathogen infection. However, RNA interference (RNAi) assay showed that LvGrx 3 silencing in ammonia-N-challenged shrimp could significantly induce the gene expression of antioxidant enzymes and aggravate the oxidative damage of protein and lipid. These results suggest that LvGrx 3 is involved in regulating the antioxidant system and plays a vital role in defense responses against environmental stress.